Contemporary Islamic Economic Thinking: A Sharia-Based Work Culture Reconstruction - Muhammad Djakfar (Karsa: Journal of Social and Islamic Culture, 2016)
The world has three existing economic systems, derived from human thinking product (science) and God’s word. The first leads to secular capitalist and soci-alist system, and the second leads to a transcendent sharia-based economy. In reality, the secular system is not able to provide a fair welfare. In fact, it often triggers human problems. In this matter, the only system able to provide solution is a system derived from God’s word. However, it is important to reveal and im-plement sharia thought from God’s word to make society knowing, under-standing, and applying it in their life. The study is a library research which data are collected using documentary method. The result of the study shows that al-Qardlâwî’s thinking is purely based on God’s word using mu’âmalah, fiqh, and akhlâq approach. Meanwhile, Chapra tries to cover how the work practice of con-ventional economy and compare it to Islamic system, and tries to offer solution using scientific approach and Islamic values. The relevance of both thinkings is that they are able to provide Islamic values in the economic development, which is lack of spiritual content.Copyright (c) 2016 by KARSA. All right reserved  DOI: 10.19105/karsa.v24i2.1127